2018
DOI: 10.1073/pnas.1721495115
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous density fluctuations in a strange metal

Abstract: A central mystery in high-temperature superconductivity is the origin of the so-called strange metal (i.e., the anomalous conductor from which superconductivity emerges at low temperature). Measuring the dynamic charge response of the copper oxides, [Formula: see text], would directly reveal the collective properties of the strange metal, but it has never been possible to measure this quantity with millielectronvolt resolution. Here, we present a measurement of [Formula: see text] for a cuprate, optimally dope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
123
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(153 citation statements)
references
References 46 publications
(71 reference statements)
14
123
0
Order By: Relevance
“…The fitting for x = 0.17 is plotted as the light pink line in Figure 1(c), which agrees with the RIXS measurements quite well. With the fitted p 1 and p 2 , the plasmon energy for x = 0.17 at q = 0 is calculated to be 1.24 eV, which is consistent with infrared optical and EELS measurements [9,29,44].…”
Section: Microscopic Consideration Of the Collective Excitationssupporting
confidence: 82%
“…The fitting for x = 0.17 is plotted as the light pink line in Figure 1(c), which agrees with the RIXS measurements quite well. With the fitted p 1 and p 2 , the plasmon energy for x = 0.17 at q = 0 is calculated to be 1.24 eV, which is consistent with infrared optical and EELS measurements [9,29,44].…”
Section: Microscopic Consideration Of the Collective Excitationssupporting
confidence: 82%
“…There we impose Dirichlet boundary conditions on all fields except δA x , on which we instead impose (2.6). As the system is linear, requiring four boundary conditions on a linear combination of four independent solutions can be rephrased as evaluating the determinant of the corresponding matrix of boundary values, and find for what values of (ω, k) that the determinant, δg ty (z) 1 δg xy (z) 1 δΦ y (z) 1 [ ω 2 − k 2 δA x (z) + λ δA x (z)] 1 δg ty (z) 2 δg xy (z) 2 δΦ y (z) 2 [ ω 2 − k 2 δA x (z) + λ δA x (z)] 2 δg ty (z) 3 δg xy (z) 3 δΦ y (z) 3 [ ω 2 − k 2 δA x (z) + λ δA x (z)] 3 δg ty (z) 4 δg xy (z) 4 δΦ y (z) 4 [ ω 2 − k 2 δA x (z) + λ δA x (z)] 4 z→0 = 0 , (A.5)…”
Section: A1 Numerical Methodsmentioning
confidence: 99%
“…It is well-established by now that strongly correlated electron systems, in particular high temperature superconductors and strange metals, display anomalous phenomenology [1]; the charge density response is not an exception. For instance, recent momentum resolved electron energy-loss spectroscopy (M-EELS) experiments found that the spectrum of cuprate strange metals cannot be understood in terms of the conventional physics of a coherent plasmon [2,3]. These unconventional condensed matter systems require unconventional theoretical approaches to describe their phenomenology and the holographic duality provides a suitable framework for this task [4].…”
Section: Introductionmentioning
confidence: 99%